Newspaper Leg Exercise to Reduce the Type 2 Diabetes Mellitus Physical Symptoms - Destu Satya Widyaningsih; Albherta Tri Prasetyowati; Ahmad Harwanto; Sheetal Goenka (Journal of Health Sciences and Medical Development, 2022)
This study aimed to determine the differences in paper leg exercise to reduce the symptoms of Type 2 DM in Elderly Family Guidance Center in Indonesia. This study used a pre-experimental method with a one-group pretest-posttest design. Inclusion criteria were the elderly who were more than 45 years old. All respondens are notready diagnosed with diabetes. The research subjects became one group and then data collection and measurements were carried out before and after being given newspaper gymnastics treatment. This is intended to be able to find out the differences experienced by the subject before and after being given treatment. Data analysis using Wilcoxon. The mean value for the pretest is 1.65 and for the posttest is 0.01. The mean between the two shows results that have different differences.. The results of Wilcoxon's analysis showed a significance differences. Its means that paper leg exercise can provide a significant difference in reducing physical symptoms of Type 2 DM. There were differences between the pretest and posttest. This shows that exercise can significantly reduce the physical symptoms of diabetes millitus in the elderly.